Does financial inclusion moderate the effect of digital transformation on banks' performance in China? - Fan Yang; Tajul Ariffin Masron (Cogent Economics & Finance, 2023)
Digital transformation remains a passion. Globally, science and technology are transforming businesses to make them more competitive and conducive to sustainable development. However, rapid advancements in financial technology have enabled financial institutions to steal customers from traditional banks, resulting in their demise. Consequently, this study employs the System GMM-two step estimator and data from 118 Chinese banks from 2014 to 2021 investigate the issue. Empirical evidence suggests that banks' digital transformation has a negative impact on their profitability to some extent, but digital inclusive finance has enabled the bank to change its digital transformation behavior and enhance its operational performance. Therefore, banks must continue to strengthen their digital transformation by expanding online customer services, increasing the use of e-accounts and mobile applications, providing digital offline services, strengthening digital risk management and privacy and security controls, reducing customer psychological risk, and promoting financial inclusion. Financial inclusion should simultaneously achieve reduced financial exclusion of customers and increased financial literacy of customers. All these factors will help banks to maintain profitability by leveraging synergies with financial inclusion in the process of digital transformation.
Keywords: 330; China; commercial bank; digital transformation; financial inclusion; GMM; profitability